2001
DOI: 10.1086/319056
|View full text |Cite
|
Sign up to set email alerts
|

Radio Supernova 1987A at 843 MHz

Abstract: We report here the Ñux densities of the evolving radio source SN

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…These plots show that the continued increase in flux density observed at 843 MHz by Ball et al (2001) is also observed at higher frequencies. The increase in slope observed at about day 2900 in the MOST data is also seen in the ATCA data ( Figure 1).…”
Section: Evolution Of Radio Flux Densities and Spectral Indexmentioning
confidence: 62%
See 3 more Smart Citations
“…These plots show that the continued increase in flux density observed at 843 MHz by Ball et al (2001) is also observed at higher frequencies. The increase in slope observed at about day 2900 in the MOST data is also seen in the ATCA data ( Figure 1).…”
Section: Evolution Of Radio Flux Densities and Spectral Indexmentioning
confidence: 62%
“…In this paper, we extend the ATCA observational database from 1995 to February 2001 (day 5100) and discuss these results in conjunction with those of Ball et al (2001). The evolution of the radio flux densities is discussed in Section 2.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, the optical hot spots, which are the inward-protruding dense gas shocked by the blast wave (Pun et al 2002;Sugerman et al 2002), show no correlation in position to the radio lobes (Manchester et al 2002). Although the emergence of the optical hot spots coincided with the arrival of the radioproducing shock at those regions ( Ball et al 2001), Manchester et al (2002) indicate that this had little effect on the morphology of the radio remnant.…”
Section: Introduction Sn 1987a In the Largementioning
confidence: 99%